Renal tubular dysfunction in children with sickle cell disease - Mohamed El Koumi; Yasser Fathy Ali; Salah El Morshedy; Asmaa Samir (Mediterranean Journal of Hematology and Infectious Diseases)
Background: Children with sickle cell disease (SCD) are remarkably more prone than others to renal dysfunction. The kidneys, as a part of the systemic long term hazards in SCD, may be affected by both the hemodynamic changes of chronic anemia as well as by the consequences of vaso-occlusion. Objective: The aim of this study was to evaluate the proximal tubular function in a group of Saudi children with established SCD. Methods: This study was conducted in Al-Khafji Joint Operations (KJO) Hospital, in Saudi Arabia, between mid-2011 and 2012. A case-control study design was conducted including two groups. Urinary excretion of retinol binding protein (RBP) and ß2- microglobulin were checked in 34 children (18 males and 16 females) with SCD (Group I), and in 27 children with sickle cell trait matched as controls (Group II). Results: Group I showed a significantly impaired urinary concentrating ability compared to the Group II (417 ± 94 mOsm/kg vs 581±165 mOsm/kg). The urinary excretion of RBP and ß2-microglobulin was significantly higher in Group I than in Group II. The values being 762.01±124.20 µg/l and 841.84±389.02 µg/l versus 198.12±42.24 µg/l and 298.3±38.11 µg/l respectively. Conclusion: Significant proximal tubular dysfunction was a feature in SCD group, indicated by high urinary RBP and ß2-microglobulin excretion. Evaluating the urinary excretion of these low molecular weight proteins, particularly RBP, may add a key clinical information to the follow up of renal tubular function in patients with SCD.